A study on the radio base station 2000 - Harun, H. (University Malaysia Sarawak, UNIMAS., 2002)
The intention of this paper is to give an introduction on the structure of Radio Base Station 2000 cabinet, the components used in the cabinets, systems used and trouble shooting that occur at site based on the research at a telecommunication company.